Age-specific health-related quality of life in long-term and very long-term colorectal cancer survivors versus population controls: a population-based study - Thong, Melissa S. Y.; Brenner, Hermann; Arndt, Volker (Acta oncologica, 2019)
Background: Previous research suggests an age differential in health-related quality of life (HRQOL) among long-term (5-10 years post-diagnosis, LTS) colorectal cancer (CRC) survivors. Few studies have specifically addressed the association of age differentials with HRQOL for very long-term CRC survivors (>10 years post-diagnosis, VLTS) and non-cancer population controls. We aimed to assess possible deficits in HRQOL of disease-free CRC-LTS and CRC-VLTS in comparison with non-cancer population controls, and whether the observed pattern varies by age and time since diagnosis. Methods: We used data from the CAncEr Survivorship - A multi-Regional (CAESAR+) study in collaboration with five population-based German cancer registries. HRQOL from controls was accessed from the Lebensqualität in DEeutschland (LinDE) study. All respondents completed the European Organization for Research and Treatment of Cancer Quality of Life Core-30 questionnaire. We calculated least square means of HRQOL scores. Analyses were adjusted for age, sex, and education, where appropriate. Results: The sample included 862 CRC-LTS, 400 CRC-VLTS and 1689 controls. CRC survivors reported overall good HRQOL but significantly poorer social functioning and more problems with dyspnea, constipation, diarrhea and finances than controls. When stratified by age, deficits in functioning and global health, and more problems with symptoms and finances were noted mainly among younger CRC survivors. Further stratification by time since diagnosis showed that similar deficits in HRQOL and symptoms were noted mainly among the younger CRC-LTS group when compared with controls. Generally, CRC-VLTS reported comparable HRQOL to controls. An exception was noted for diarrhea, whereby CRC survivors, regardless of age and time since diagnosis, reported significantly more problems with this symptom than controls. Conclusions: In comparison with non-cancer controls, disease-free CRC survivors reported overall good HRQOL but experience persistent specific detriments in HRQOL many years after diagnosis. In age stratified analyses, HRQOL deficits were noted mainly among younger CRC-LTS.